Helminth infections and cardiovascular diseases: A role for the microbiota and Mϕs?. Issue 6 (1st September 2021) - Lin, Jian-Da; Loke, P'ng
Abstract: Cardiovascular diseases are rising in developing countries with increasing urbanization and lifestyle changes and remains a major cause of death in the developed world. In this mini review, we discuss the possibility that the effect of helminth infections on the immune system and the microbiota may affect risk factors in cardiovascular diseases such as atherosclerosis, as part of the hygiene hypothesis. The effects of Type 2 immune responses induced by helminths and helminth derived molecules on regulating metabolism and Mϕ function could be a mechanistic link for further investigation. We emphasize the complexity and difficulties in determining indirect or direct and causal relationships between helminth infection status and cardiovascular diseases. New experimental models, such as rewilding laboratory mice, whereby different aspects of the environment and host genetics can be carefully dissected may provide further mechanistic insights and therapeutic strategies for treating cardiovascular diseases. Graphical Abstract: Reviews helminth infection's impact on the immune system and the microbiota; provides mechanistic insight that may aid in finding new approaches for treating cardiovascular disease.